Proximal hamstring tendon avulsion treatment choice depends on a combination of clinical and imaging-related factors: a worldwide survey on current clinical practice and decision-making. Issue 4 (12th July 2019) - van der Made, Anne D; Hölmich, Per; Kerkhoffs, Gino M M J; Gouttebarge, Vincent; D'Hooghe, Pieter; Tol, Johannes L
Abstract : Objectives: To evaluate current practice in the treatment of proximal hamstring tendon avulsions and identify decision-making preferences. Methods: An invitation to an anonymous e-survey containing 32 questions was sent to 3475 members of the International Society of Arthroscopy, Knee Surgery and Orthopaedic Sports Medicine (ISAKOS) and the European College of Sports and Exercise Physicians (ECOSEP). Results: We received 403 (12%) unique responses with a completion rate of 79%. Participants were orthopaedic/trauma surgeons (90%), sports medicine physicians (7%) or physical therapists (2%). For 83% of the participants, the preferred treatment (ie, surgical or non-operative) depends on the individual case. Participants base their decision-making process on patient- and injury-related factors (decision modifiers). The five most frequently selected decision modifiers that support the choice for surgical treatment were diminished function (84%), neurological symptoms (74%), involved tendons (82%), tendon retraction on MRI (84%) and patient preference for surgery (78%). The majority prefer early surgical repair (<2 weeks after injury) to achieve highest functional outcome (63%) and ensure a low complication risk (61%). Suture anchors are used by 93% of the participants for tendon reattachment. Estimated recovery duration (ie, time to return to sports) was a median 12 weeks (IQR: 12–20) for non-operative treatment and 17 weeks (IQR: 12–24) for surgical treatment. Estimated reinjury risk was a median 25% (IQR: 10–31.5) and 10% (IQR: 5–20), respectively. Conclusion: This survey among experienced medical professionals has summarised current practice and identified treatment decision-making preferences. The typical surgical patient has a retracted (>2 cm) two-tendon avulsion (ie, common tendon and semimembranosus tendon), is unable to engage in sports or activities of daily life, reports sciatic symptoms and prefers surgical treatment. Surgery is thought to prolong recovery and decrease reinjury risk compared with non-operative treatment and is preferably performed early. Level of evidence: Level V.